Design and optimization of heat pump with infrared drying for Glycyrrhiza uralensis (Licorice) processing - Zhu, Lichun; Xie, Yongkang; Li, Mengqing; Zhang, Xuetao; Ji, Xinyu; Zhang, Xiaoqiang; Zhu, Hongbo; Gu, Junzhe; Zhang, Qian; Yang, Xuhai (Frontiers in Nutrition, 2024)
A new dryer, integrating infrared and heat pump drying technologies, was designed to enhance licorice processing standardization, aiming at improved drying efficiency and product quality. Numerical simulation using COMSOL software validated the air distribution model through prototype data comparison. To address uneven air distribution, a spoiler was strategically placed based on CFD simulation to optimize its size and position using the velocity deviation ratio and non-uniformity coefficient as indices. Post-optimization, the average velocity deviation ratio decreased from 0.5124% to 0.2565%, and the non-uniformity coefficient dropped from 0.5913 to 0.3152, achieving a more uniform flow field in the drying chamber.Testing the optimized dryer on licorice demonstrated significant improvements in flow field uniformity, reducing licorice drying time by 23.8%. Additionally, optimized drying enhanced licorice color (higher L* value) and increased retention rates of total phenol, total flavone, and vitamin C. This research holds substantial importance for advancing licorice primary processing, fostering efficiency, and improving product quality.